Answer:
(33,-260)
Explanation:
y=2(3)².....equation(1)
y=2/3x -4 ...equation(2)
put equation(1) to equation(2)
2(3)² = 2/3x - 4
2(9)= 2/3x - 4
18 = 2/3x - 4
add 4 to both sides
18+4 = 2/3 x- 4 +4
22 = 2/3x
multiply via by 3
22×3 = 2/3x × 3
66 = 2x
divide both sides by 2
66/2 = 2x/2
33 = x
x=33
solve for y
to solve for y, put x in equation (2)
y=2/3x - 4
y = 2/3(33) - 4
y = 2/66 - 4
find the LCM of 66 and 1
the LCM is 66
multiply by their LCM
y = (2/66)66-4×66
y = 2 - 264
y = -260
solution= (33,-260)